Niezależność zawodowa biegłego rewidenta w kontekście nadzoru korporacyjnego na tle regulacji krajowych i europejskich - Bogacz-Miętka, Olga (The Independence of Auditor in the Context of Corporate Governance against the Background of Polish and European Regulations, 2007)
Financial scandals, which had taken place at the turn of the XX/XXI century and had been connected with the falsification of accounts, caused the significant fall of the confidence of investors in capital markets all over the world and reduction of credibility of the auditor's profession. These all contributed to the discussion on necessity of the shaping the ethical attitudes, reinforcement of the supervision the accountancy and auditing, reforming the financial reporting standards and propagating the best practices of corporate governance. The aim of this paper is to present the issues connected with the role, which plays the independence of auditor in endorsing the accountanting statement. The paper also shows the relationship between the quality of the audit and quality of the corporate governance. The article presents regulations of the Polish Accounting Act and just reformed VIII Directive of the EU, which concern the issue of the independence of auditor, and the postulates of the domestic Codes of Best Practices in this scope.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 29-42